Does timing matter? The role of health information shocks in measuring willingness to pay - Carolin Brinkmann; Sebastian Neumann-Böhme; Werner B. F. Brouwer; Tom Stargardt (The European Journal of Health Economics, 2025)
Objectives: The optimal point in time to measure willingness-to-pay (WTP) remains unclear. We investigated the role of health information shocks (HIS) in individuals' WTP, analyzing the extent to which news of SARS-CoV-2 infections among people they know/themselves altered WTP for booster vaccinations. Methods: We elicited WTP in eight European countries using the European Covid Survey. First, we presented participants with a hypothetical setting recommending a booster vaccination that had to be paid out-of-pocket. To measure WTP, we elicited a lower and upper WTP limit, and a WTP value contingent on both of these. To measure HIS, we asked about the duration since participants received news of COVID-19 cases among people they know (including themselves), as well as the degree of personal connection to these cases and their severity. We used a two-part model to estimate the association between HIS and individuals' WTP. Results: Among the 5809 observations, 76.8% stated a WTP for a booster vaccination greater than exteuro0. At least one HIS was reported by 61.9% of participants. The occurrence of a HIS was associated with an increase in WTP of exteuro14.54 (logistic: P <.0001, gamma: P =.1493) compared to no HIS. The WTP was higher when the HIS occurred in the four weeks before the survey. Controlling for socio-demographic and COVID-19 covariates decreased significance and effect sizes. Conclusion: Our findings suggest that a recent HIS is associated with a higher probability of having a positive WTP. Timing, in relation to some relevant event, therefore may matter when measuring WTP for health interventions. If so, finding the optimal point in time to measure WTP is difficult and may depend on the policy question under consideration.
Keywords: I10; I12; 610; Willingness to pay; Information shock; Health shock; Vaccination